Situation Report: Bulgaria, 6 February 1962 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Warsaw Pact Meeting in Prague Talks on Nish-Dimitrovgrad Highway Improvement Recent Bulgarian-Romanian Talks Trade Agreement for 1962 Bulgarian-Czechoslovak Scientific Collaboration National Conference on Home and Foreign Trade The Trade Unions to Cooperate with State Departments